POSITIVE EMOTIONS: FACTORS INFLUENCING KNOWLEDGE SHARING AMONG SOFTWARE INDUSTRY TEAM MEMBERS (Interdisciplinary Studies Journal, 2025)
Knowledge Management (KM) is an interdisciplinary discipline that proposes ways for an organization to capture, structure, and disseminate knowledge. This knowledge can be developed in the organizational environment, in an appropriate space for the interaction of individuals and sharing in groups. However, other variables can influence the interaction with individuals, one of which may be positive emotions, such as joy, interest, love, and contentment. In this context, the objective of this article is to investigate the factors that influence positive emotions in knowledge sharing among members of the software development team. This research has an applied nature with an exploratory and descriptive objective, in which it comprises the mixed approach and technical procedures of bibliographic survey and field research. A questionnaire was applied, followed by interviews with members of software development teams. The results demonstrate four factors that stimulate the internalization of positive emotions: organizational factor, physical infrastructure factor, collaboration factor, and leadership factor for team integration. In turn, we observed that positive emotions of cheer, contentment, fun, happiness, strength, gratitude, inspiration, pride, optimism, and patience influence the sharing of organizational knowledge.
Keywords: Knowledge management; Knowledge dissemination; Software Engineering; Well-being